Silicon Heterojunction Solar Cells: Towards Low-cost High-Efficiency Industrial Devices and Application to Low-concentration PV. (August 2015) - Descoeudres, Antoine; Allebé, Christophe; Badel, Nicolas; Barraud, Loris; Jonathan Champliaud,; Debrot, Fabien; Faes, Antonin; Lachowicz, Agata; Levrat, Jacques; Nicolay, Sylvain; Sansonnens, Laurent; Despeisse, Matthieu; et al.
Abstract: The silicon heterojunction (SHJ) technology has already proven its ability to produce high-efficiency devices, and very competitive production costsat the mass production level can be potentially reached by integrating latest developments. In this work, several of such technology developments are presented related to the PECVD and metallization steps. PECVD processes were developed in a large-area reactor, showing excellent thickness uniformity over the full reactor area (< 4%) and state-of-the-art passivation level (> 16 ms). Improvements in screen-printing permitted to reduce the finger width down to 40 μm. A 21.9% 6-inch busbar-less cell with only 25 mg of Ag was produced, resulting in Ag cost of only 0.22 €cts/Wp. A complete SHJ process for full-area 6-inch cells has been established using industry-compatible processes, with a record efficiency of 22.8% and Voc s above 740 mV (CZ n -type). The use of 4 cm 2 SHJ cells for low-concentration applications was investigated at different illumination levels and temperatures. With optimized front grid designs (Cu electro-plated fingers), efficiencies can be maintained around 20% at 10 suns. Thanks to a temperature-assisted improvement in carrier transport, the cell temperature coefficient improves with illumination, showing even positive values above 35 suns. This suggests a strong potential of SHJ cells for low-concentration PV.